Mean Platelet Volume as a Predictor of Left Atrial Appendage Thrombus Resistance to Lysis in Patients With Atrial Fibrillation: Results of a 12-Month Follow-Up - Tatiana P. Gizatulina; Alfira V. Belokurova; Aleksandra V. Mamarina; Natalia Yu. Khorkova; Elena A. Gorbatenko (Reviews in Cardiovascular Medicine, 2025)
Background: Left atrial appendage thrombosis (LAAT), a contraindication to catheter ablation (CA), is a major problem in patients with non-valvular atrial fibrillation (AF). This study aimed to investigate the dynamics of LAAT and identify the factors associated with resistance to LAAT resolution over a 12-month period. Methods: A total of 83 of the 2766 patients with AF who underwent transesophageal echocardiography (TEE) before CA (median age, 62 years; 49 men) participated in follow-up studies. All patients received oral anticoagulants (OACs) and underwent a general clinical examination, which included a complete blood count, biochemical tests, and transthoracic echocardiography. In total, 39 patients (47%) had paroxysmal AF, and 44 patients (53%) had persistent AF. Results: Patients were divided into two groups based on dynamic TEE monitoring: Group 1 (n = 45), comprising patients whose LAAT resolved within 12 months, and Group 2 (n = 38), consisting of patients whose LAAT persisted until the end of the follow-up study. No significant differences were observed in age, sex, and incidence of cardiovascular disease between the groups. However, Group 2 patients were more likely to administer beta-blockers, diuretics, and rivaroxaban at the start of the study. The OACs were altered in 65 patients due to the repeated detection of LAAT. Comparative analysis revealed that Group 2 patients had higher right atrial volume index, N-terminal pro-brain natriuretic peptide (NT-proBNP) levels, mean platelet volume (MPV), platelet distribution width, and platelet–large cell ratio. Multivariate logistic regression analysis was used to derive a prediction model for LAAT resistance, which included three independent predictors: diuretics intake (odds ratio (OR) 3.800, 95% confidence interval (CI) 1.281–11.275; p = 0.016), NT-proBNP level (OR 1.001, 95% CI 1.000–1.001; p = 0.015), and MPV (OR 1.892, 95% CI 1.056–3.387; p = 0.032). The receiver operating characteristic (ROC) analysis confirmed the good quality of the model: Area under the ROC curve (AUC) 0.789, specificity 72.7%, and sensitivity 73.3%. Conclusions: This study confirmed that approximately 47% LAAT remains resistant to lysis 1 year after initial detection in patients with AF, regardless of the use of OACs. To our knowledge, this is the first time that platelet morphofunctional parameters, particularly MPV, have been identified as predictors of LAAT lysis resistance, and further research in this direction is needed.